Pengaruh Suhu dan Tekanan terhadap Hasil Penggorengan Keripik Ubi Cilembu (Ipomoea batatas) Menggunakan Vacuum Frying - Asmara, Sandi; Kuncoro, Sapto; Tamrin, Tamrin; Nahak, Gradiana Eny (abe.fp.unila.ac.id, 2024)
Cilembu sweet potato production in Lampung reached 28,494,000 tons/year (2015 statistical data). The selling price of Cilembu sweet potatoes in traditional markets is low, ranging from IDR 4,000 to IDR 10,000/Kg. Therefore, it is necessary to carry out appropriate processing in order to increase the selling price of Cilembu sweet potatoes. One way that can be done is by making Cilembu sweet potatoes into a chips product using a Vacuum Frying fryer. A vacuum fryer is a vacuum fryer which has the advantage of frying fruit and vegetables into crispier chips and maintaining product quality without preservatives. The aim of this research is to analyze the influence of temperature and pressure on the results of frying Cilembu sweet potato chips using a Vacuum Frying fryer and determine the optimal temperature and pressure needed to produce the best quality Cilembu sweet potato chips. The research method used was a factorial Completely Randomized Design (CRD). The experimental factors in this study used two factors, temperature (T), namely 80°C, 85°C, 90°C and pressure (P) -66 cmHg, -68 cmHg, -70 cmHg, with repetition 3 times to produce 27 experimental units. The parameters observed were material weight loss analysis (random), water content, and sensory tests. It can be concluded that the optimal choice of temperature and pressure in operating the Vacuum Frying tool for frying Cilembu sweet potato chips is a temperature of 90°C and a pressure of -68 cmHg. The quality of frying pans with a temperature of 90°C and a pressure of -68 cmHg is included in the best product category in this research based on overall acceptance which has a yield value of 35%, water content of 3.3%, and a color sensory test score of 3.75 (yellow), aroma 2.95 (the aroma of Cilembu sweet potato chips is a bit strong), taste 4.25 (like it), crunchiness 4.2 (crisp). Keywords: Chips, Cilembu Sweet Potato, Vacuum Frying.